2020
DOI: 10.1029/2020gh000271
|View full text |Cite
|
Sign up to set email alerts
|

The Disappearing Lake: A Historical Analysis of Drought and the Salton Sea in the Context of the GeoHealth Framework

Abstract: The Imperial Valley region of Southeastern California has become one of the most productive agricultural regions in the state and has the highest rates of childhood asthma in California. Lack of precipitation in the Imperial Valley has caused the water level of the Salton Sea to recede to a record low since its formation in the early 1900s. Previous studies of wind and dust deposition conducted in other regions have shown how reduced precipitation, ground heating, and the diminishing water level in an arid cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Salton Sea depletion was primarily caused by the decline in major tributaries inflows (i.e., New and Alamo Rivers and East Highline Canal). Several studies and reports (Barnum et al., 2017; Cohen, 2014; Congressional Research Service, 2021; Doede & DeGuzman, 2020; Scott et al., 2014) suggested that decline in the lake inflows is mostly due to four reasons: (a) Lack of precipitation due to drought, (b) decreasing agricultural return flows caused by more efficient irrigation methods in the Imperial Valley, (c) decline in flows from Mexico, and (d) increasing water transfers to San Diego County. The latter can only affect the SSTB water balance through direct reductions in the Colorado River allocations, causes of which are out of the scope of this study as the Colorado River Aqueduct transfers water to San Diego County from the Lake Havasu in Arizona.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salton Sea depletion was primarily caused by the decline in major tributaries inflows (i.e., New and Alamo Rivers and East Highline Canal). Several studies and reports (Barnum et al., 2017; Cohen, 2014; Congressional Research Service, 2021; Doede & DeGuzman, 2020; Scott et al., 2014) suggested that decline in the lake inflows is mostly due to four reasons: (a) Lack of precipitation due to drought, (b) decreasing agricultural return flows caused by more efficient irrigation methods in the Imperial Valley, (c) decline in flows from Mexico, and (d) increasing water transfers to San Diego County. The latter can only affect the SSTB water balance through direct reductions in the Colorado River allocations, causes of which are out of the scope of this study as the Colorado River Aqueduct transfers water to San Diego County from the Lake Havasu in Arizona.…”
Section: Resultsmentioning
confidence: 99%
“…Salton Sea depletion was primarily caused by the decline in major tributaries inflows (i.e., New and Alamo Rivers and East Highline Canal). Several studies and reports (Barnum et al, 2017;Cohen, 2014;Congressional Research Service, 2021;Doede & DeGuzman, 2020;Scott et al, 2014) suggested that decline in the lake inflows is mostly due to four reasons: In order to explore interrelationships between the main lake tributary inflows, the Colorado River inflows, and valley irrigation volumes, a hierarchical time series clustering approach was implemented to partition trend and seasonal components of variables into groups based on dynamic time warping similarity. Therefore, time series within a same cluster have similar patterns over time.…”
Section: Interrelationships Among Lake Depletion Irrigation and Impor...mentioning
confidence: 99%
“…Drought is a periodic and growing natural disaster that impacts extensive subject areas [1], including water resources [2,3] and crop yield [4][5][6], as well as a range of environmental systems [7], resulting in serious harm to ecological security and human society [8,9]. Over the past half-century, drought has become more and more serious all over the world [10], which has greatly reduced the productivity of grazing grasslands and artificial mowed grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…The fine dry playa sediments of the shallow Great Salt Lake (GSL) to the northwest, the West Desert playa to the west, and Sevier Dry Lake playa to the south have been implicated as dust sources (Carling et al., 2020 ; Goodman et al., 2019 ; Skiles et al., 2018 ). Like other saline lakes globally, extractive water uses are shrinking the GSL (Doede & DeGuzman, 2020 ; Mallia et al., 2017 ; Wurtsbaugh et al., 2017 ). Local and national news coverage of the issue has highlighted that the expanding and increasingly weathered dry lakebed may increase fluxes of arsenic (As)—and other metal‐laden dust, further degrading already problematic air quality in the Central Wasatch (Flavelle, 2022 ; Kafanov, 2021 ; Spencer, 2021 ).…”
Section: Introductionmentioning
confidence: 99%